Biphasic Action of Aldosterone on Akt Signaling in Cardiomyocytes - Nagoshi, T.; Date, T.; Fujisaki, M.; Yoshino, T.; Sekiyama, H.; Ogawa, K.; Kayama, Y.; Minai, K.; Komukai, K.; Ogawa, T.; Yoshimura, M. (Hormone and Metabolic Research, 2012)
Both aldosterone and Akt signaling play pivotal roles in the pathogenesis of heart failure. However, little is known about the correlation between them. We herein investigated whether aldosterone interacts with Akt signaling in a coordinated manner in cardiomyocytes. Neonatal rat cardiomyocytes were stimulated with aldosterone for either a short (10-min) or long (24-h) time. The phosphorylation of Akt and its downstream effector, GSK3β, were transiently increased after short-term stimulation, which was blocked by either PI3K or Na+/H+ exchanger inhibitors, but not by the mineralocorticoid receptor antagonist, eplerenone. Long-term stimulation also significantly increased Akt-GSK3β phosphorylation and this effect was reduced by eplerenone. Thus, these results suggest that aldosterone activates Akt signaling via a biphasic reaction that occurs through different cascades. To understand the significance of the rapid action of aldosterone, cardiomyocytes were exposed to hydrogen peroxide for from 10 to 60 min. A short-term aldosterone stimulation (for up to 30 min) significantly protected cardiomyocytes from oxidative stress-induced cellular damage. Eplerenone did not abrogate this beneficial effect, while a PI3K inhibitor did. Therefore, during the early phase, aldosterone has favorable effects on cardiomyocytes, partly by acute activation of a mineralocorticoid receptor-independent cascade through the Na+/H+ exchanger, PI3K, and Akt. In contrast, its persistent activity produces pathological effects partly by chronic Akt activation in a mineralocorticoid receptor-dependent manner.
Keywords: aldosterone; insulin; cardiomyocyte; Akt; mineralocorticoid receptor; Na+/H+ exchanger-1